Marcona mining port management and its development objective on underwater life - Ramírez Caján, Alfonso (2022)
This research is carried out within the scope of the modernization of the Port System of San Juan de Marcona, whose sustainability approach based on the growth of port activities and the protection of the marine environment, is linked to the operations carried out by the Shougang mining companies and Marcobre, through the management and handling of solid waste and oily mixtures that they receive from ships at their terminals. The objective was to analyze the cycle of waste from its source of generation to its disposal, to know the state of environmental conditions presented by coastal waters and the impact on aquatic ecosystems. The methodology presented an explanatory investigation, identifying the number of existing aquatic and terrestrial reception facilities in the jurisdiction, the result of which revealed the scarce infrastructure and limited capacity for the temporary storage of waste, concluding that the risks of marine pollution and aquatic biota, significantly affect underwater life, fishing, tourism, and protected areas.